Dynamic consumption representation of electric vehicles based on battery capacity (2018)
This paper presents a methodology for generating different charge characteristics using probability function of battery capacity and Tremblay non-linear battery electric model. The battery capacities are grouped into five categories to obtain a behavior of the charging curve variable over time and to determine the probability function of discharged energy. The charging curves of each electric vehicle will represent instantaneous power consumption in a low voltage distribution system with 56 nodes and will allow the comparison between the proposed methodology and the case that considers a linear characteristic of battery charging curve.